2014
DOI: 10.1111/idj.12088
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis prescribing practices of dentists in Singapore

Abstract: Dentists were accurate in their prescriptions of antibiotic prophylaxis for dental procedures, but not for cardiac conditions. It may be helpful to attain a consensus among local cardiologists and dentists to unify the antibiotic prophylaxis prescription practices in Singapore.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 22 publications
3
33
0
Order By: Relevance
“…These results are encouraging as they are higher than the percentage of dentists determined to be following the 2007 AHA guidelines by researchers Tong et al 26 (40%) and Coutinho et al 28 (33%). However, our study found that 36% of dentists preferred to follow the patient's physician/specialist orders.…”
Section: Discussionmentioning
confidence: 68%
See 4 more Smart Citations
“…These results are encouraging as they are higher than the percentage of dentists determined to be following the 2007 AHA guidelines by researchers Tong et al 26 (40%) and Coutinho et al 28 (33%). However, our study found that 36% of dentists preferred to follow the patient's physician/specialist orders.…”
Section: Discussionmentioning
confidence: 68%
“…The questionnaire for our investigation was a modified version of a survey developed by Tong et al 26 Our survey consisted of 25 questions containing multiple choice, yes/no response, and space for additional comments.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations